Structural diversity of solid dispersions of acetylsalicylic acid as seen by solid-state NMR - Policianova, Olivia; Brus, Jiri; Hruby, Martin; Urbanova, Martina; Zhigunov, Alexander; Kredatusova, Jana; Kobera, Libor (Molecular pharmaceutics, 2014)
Solid dispersions of active pharmaceutical ingredients are of increasing interest due to their versatile use. In the present study polyvinylpyrrolidone (PVP), poly[N-(2-hydroxypropyl)-metacrylamide] (pHPMA), poly(2-ethyl-2-oxazoline) (PEOx), and polyethylene glycol (PEG), each in three Mw, were used to demonstrate structural diversity of solid dispersions. Acetylsalicylic acid (ASA) was used as a model drug. Four distinct types of the solid dispersions of ASA were created using a freeze-drying method: (i) crystalline solid dispersions containing nanocrystalline ASA in a crystalline PEG matrix; (ii) amorphous glass suspensions with large ASA crystallites embedded in amorphous pHPMA; (iii) solid solutions with molecularly dispersed ASA in rigid amorphous PVP; and (iv) nanoheterogeneous solid solutions/suspensions containing nanosized ASA clusters dispersed in a semiflexible matrix of PEOx. The obtained structural data confirmed that the type of solid dispersion can be primarily controlled by the chemical constitutions of the applied polymers, while the molecular weight of the polymers had no detectable impact. The molecular structure of the prepared dispersions was characterized using solid-state NMR, wide-angle X-ray scattering (WAXS), and differential scanning calorimetry (DSC). By applying various (1)H-(13)C and (1)H-(1)H correlation experiments combined with T1((1)H) and T1ρ((1)H) relaxation data, the extent of the molecular mixing was determined over a wide range of distances, from intimate intermolecular contacts (0.1-0.5 nm) up to the phase-separated nanodomains reaching ca. 500 nm. Hydrogen-bond interactions between ASA and polymers were probed by the analysis of (13)C and (15)N CP/MAS NMR spectra combined with the measurements of (1)H-(15)N dipolar profiles. Overall potentialities and limitations of individual experimental techniques were thoroughly evaluated.
Keywords: Aspirin; suspenze; Molecular Structure; Calorimetry, Differential Scanning; Magnetic Resonance Spectroscopy; magnetická rezonanční spektroskopie; diferenciální skenovací kalorimetrie; Suspensions; molekulární struktura